Pulmonary clearance of vasoactive intestinal peptide. Issue 2 (February 1986) - Barrowcliffe, M P; Morice, A; Jones, J G; Sever, P S
Abstract : Vasoactive intestinal peptide causes bronchodilatation when given intravenously but is less effective in both animals and man when given by inhalation. This difference may be due to poor transit of the peptide across the bronchial epithelium. To test this hypothesis pulmonary clearance of radiolabelled vasoactive intestinal peptide was measured in Sprague Dawley rats and compared with that of pertechnetate (TcO4-) and diethylene triamine pentaacetate (DTPA). Despite a molecular weight (MW) of 3450, iodinated vasoactive intestinal peptide was cleared rapidly from the lungs, with a mean half time (t1/2) of 19 minutes after an initial slower phase. This compares with a t1/2 of 10 minutes with TcO4- (MW 163) and a t1/2 of 158 minutes with DTPA (MW 492). The possibility that vasoactive intestinal peptide mediates a non-specific increase in permeability was discounted by the fact that the combination of vasoactive intestinal peptide and DTPA did not alter DTPA clearance significantly. Chromatography and radioimmunoassay of blood taken after intratracheal administration of vasoactive intestinal peptide demonstrated a metabolite but no unchanged peptide. An intravenous injection of the peptide disappeared on first pass through the lung. It is concluded that inhaled vasoactive intestinal peptide lacks efficacy as a bronchodilator not because of slow diffusion to airway smooth muscle but because it is metabolised at an early stage of its passage through the respiratory epithelium.